Maize centromeres expand and adopt a uniform size in the genetic background of oat - Wang, Kai; Wu, Yufeng; Zhang, Wenli; Dawe, R. Kelly; Jiang, Jiming

(untitled) (Genome Research, 2014)
Most existing centromeres may have originated as neocentromeres that activated de novo from noncentromeric regions. However, the evolutionary path from a neocentromere to a mature centromere has been elusive. Here we analyzed the centromeres of nine chromosomes that were transferred from maize into oat as the result of an inter-species cross. Centromere size and location were assayed by chromatin immunoprecipitation for the histone variant CENH3, which is a defining feature of functional centromeres. Two isolates of maize chromosome 3 proved to contain neocentromeres in the sense that they had moved from the original site, whereas the remaining seven centromeres (1, 2, 5, 6, 8, 9, and 10) were retained in the same area in both species. In all cases, the CENH3-binding domains were dramatically expanded to encompass a larger area in the oat background (∼3.6 Mb) than the average centromere size in maize (∼1.8 Mb). The expansion of maize centromeres appeared to be restricted by the transcription of genes located in regions flanking the original centromeres. These results provide evidence that (1) centromere size is regulated; (2) centromere sizes tend to be uniform within a species regardless of chromosome size or origin of the centromere; and (3) neocentromeres emerge and expand preferentially in gene-poor regions. Our results suggest that centromere size expansion may be a key factor in the survival of neocentric chromosomes in natural populations.